2018
DOI: 10.1080/09638288.2018.1443349
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the Croatian translation of the community integration questionnaire-revised in a sample of adults with moderate to severe traumatic brain injury

Abstract: The results show that the Croatian translation of the Community Integration Questionnaire-Revised is useful in assessing participation in adults with traumatic brain injury and confirm previous findings that severity of injury predicts community integration. Results of the new Electronic Social Networking scale indicate that persons who are more active on electronic social networks report better results for other domains of community integration, especially social activities. Implications for rehabilitation Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
1
4
0
2
Order By: Relevance
“…Cronbach's alpha coefficient shows a good internal consistency for the home integration (HI) subscale only ( α = 0.82) so that we can consider it to be the most sensitive to measure community integration's level in healthy people. This result is very similar to those in other studies and validations, especially to those of the Croatian version of the CIQ-R, which was validated in healthy population and in TBI patients [ 23 ]. We can affirm that home integration subscale results to have the greatest sensitivity in measuring the level of individual's integration in family life and participation to housework's, such as shopping for groceries or other necessities, preparing meals, caring for the children, planning social arrangements (such as get-togethers with family and friends), or looking after personal finances (such as banking or paying bills).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Cronbach's alpha coefficient shows a good internal consistency for the home integration (HI) subscale only ( α = 0.82) so that we can consider it to be the most sensitive to measure community integration's level in healthy people. This result is very similar to those in other studies and validations, especially to those of the Croatian version of the CIQ-R, which was validated in healthy population and in TBI patients [ 23 ]. We can affirm that home integration subscale results to have the greatest sensitivity in measuring the level of individual's integration in family life and participation to housework's, such as shopping for groceries or other necessities, preparing meals, caring for the children, planning social arrangements (such as get-togethers with family and friends), or looking after personal finances (such as banking or paying bills).…”
Section: Discussionsupporting
confidence: 90%
“…In the last few years, the CIQ-R has been used in many researches worldwide [ 12 20 ] and translated and validated in several languages, such as Persian [ 21 ], Japanese [ 22 ], and Croatian [ 23 ]. Despite the CIQ-R's wide use and the many articles comparing the CIQ with other evaluation scales (e.g., the CHART [ 24 ], SPRS [ 25 ], CIM [ 26 ], and Functional Independence Measure (FIM) [ 27 ]), studies attesting the reliability and construct validity of the CIQ, compared to those of different tools and gold standards, are limited.…”
Section: Introductionmentioning
confidence: 99%
“…20 This is coherent with the results obtained with the traumatic brain injury population. 6,8,31 The Social Integration subscale scores for internal consistency were higher with the traumatic brain injury population than with the populations included in included studies. [17][18][19]20,22,24 Also, issues concerning the Productive Activities subscale that were first raised in studies with the traumatic brain injury populations 8,32 were also present in the studies included in this review.…”
Section: Discussionmentioning
confidence: 93%
“…Mnoga istraživanja potvrđuju da uslijed oštećenja kognitivnih, motoričkih, emocionalnih ili bihevioralnih funkcija posljedice TOM-a dugoročno utječu na samostalnost i sudjelovanje u brojnim područjima svakodnevnog života (Beadle, Ownsworth, Fleming i Shum, 2016.;Douglas, 2020;Giles i sur. 2019;Klepo, Sangster Jokić i Tršinski, 2020;Milders, 2019;Ponsford i sur., 2014;Rapport, Hanks i Bryer, 2006;Tršinski, Tadinac, Bakran i Klepo, 2019;Watkin, Phillips i Radford, 2020). TOM se vrlo često naziva i "tiha epidemija" jer posljedice ozljede na prvi pogled nisu uočljive i društvo ih uglavnom nije dovoljno svjesno (Peeters i sur.…”
Section: Uvod Traumatska Ozljeda Mozgaunclassified
“…Brain injuries are typically classified as mild, moderate, and severe based on the Glasgow Coma Scale (GCS; Teasdale & Jennett, 1974), while the consequences of such injury can range from shortterm loss of consciousness to coma or even death as a result of a traumatic event (Faul & Coronado, 2015). Several studies have confirmed that TBI can cause the impairment of cognitive, motor, emotional, and behavioural functions, subsequently affecting long-term independence and participation in many areas of daily life (Beadle, Ownsworth, Fleming & Shum, 2016;Douglas, 2020;Giles et al 2019;Klepo, Sangster Jokić & Tršinski, 2020;Milders, 2019;Rapport, Hanks & Bryer, 2006;Tršinski, Tadinac, Bakran & Klepo, 2019;Watkin, Phillips & Radford, 2020).…”
Section: Introduction Traumatic Brain Injurymentioning
confidence: 99%